(untitled) (Communications in Mathematical Research, 2021)
The nondegenerate affine locally symmetric surfaces in R^4 with the transversal bundle defined by Nomizu and Vrancken^[1] have been studied and a complete classification of the locally symmetric surfaces with flat normal bundle has been given.